Optimizing cognitive efficiency of emotiv EPOC and controlling wheelchair through it - Chowdhury, Pritom; Shakim, S. S Kibria (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.